Cerebrovascular Manifestations of Lyme Neuroborreliosis—A Systematic Review of Published Cases - Garkowski, Adam; Zajkowska, Joanna; Zajkowska, Agata; Kułakowska, Alina; Zajkowska, Olga; Kubas, Bożena; Jurgilewicz, Dorota; Hładuński, Marcin; Łebkowska, Urszula (Frontiers in Neurology, 2017)
Background: Lyme neuroborreliosis (LNB) is a disease caused by spirochaete Borrelia burgdorferi, involving the nervous system. It usually manifests as lymphocytic meningoradiculitis, but in rare cases it can also lead to cerebrovascular complications. We aimed to perform a systematic review of all reported cases of LNB complicated by central nervous system vasculitis and stroke or transient ischemic attack (TIA). Material and Methods: We conducted a systematic review of literature between May 1987 and December 2016 with patients who presented with cerebrovascular course of LNB. Results: This study included 88 patients with a median age of 46 years. The median interval from onset of symptoms suggesting Lyme disease to first symptoms of cerebrovascular manifestations of LNB was 3.5 months. The most common cerebrovascular manifestation of LNB was ischemic stroke (76.1%), followed by TIA (11.4%). The posterior circulation was affected alone in 37.8% of patients, the anterior circulation in 24.4% of patients, and in 37.8% of cases posterior and anterior circulation were affected simultaneously. The most common affected vessels were middle cerebral artery – in 19 cases, basilar artery – in 17 cases and anterior cerebral artery – in 16 cases. A good response to antibiotic treatment was achieved in the vast number of patients (75.3%). The overall mortality rate was 4.7%. Conclusions: Cerebral vasculitis and stroke due to LNB should be considered, especially in patients who live in or have come from areas with high prevalence of tick-borne diseases, as well as in those without cardiovascular risk factors, but with stroke-like symptoms of unknown cause.